2010
DOI: 10.1038/ejcn.2009.148
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant nutrient intakes and corresponding biomarkers associated with the risk of atopic dermatitis in young children

Abstract: Background/Objectives: To investigate the association of antioxidant nutritional status with the risk of atopic dermatitis (AD) in young children in a case-control, population-based study. Subjects/Methods: Identified from preschools by using the Korean version of the International Study of Asthma and Allergies in Childhood (ISAAC). Final analysis included 180 AD (mean age 5.3 ± 0.9 years) and 242 non-AD (mean age 5.2 ± 1.0 years) children. Diet was assessed using a validated semi-quantitative food frequency q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 28 publications
(34 reference statements)
6
80
1
1
Order By: Relevance
“…Impairment of the skin barrier and imbalance in the ratios of Th1/Th2 and Tregs/Th17 are key contributors to the pathogenesis of AD, suggesting a potential link between VA and AD. Recently, Oh et al [20] found that serum VA concentrations are lower in children with AD, regardless of the level ingested from food or found in the serum, and that AD was negatively associated with the intake of antioxidant-related nutrients (including VA and β-carotene). Their findings suggested that VAD increases the risk of AD, consistent with our own conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impairment of the skin barrier and imbalance in the ratios of Th1/Th2 and Tregs/Th17 are key contributors to the pathogenesis of AD, suggesting a potential link between VA and AD. Recently, Oh et al [20] found that serum VA concentrations are lower in children with AD, regardless of the level ingested from food or found in the serum, and that AD was negatively associated with the intake of antioxidant-related nutrients (including VA and β-carotene). Their findings suggested that VAD increases the risk of AD, consistent with our own conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…However, few reports have explored the correlation between AD and VA to date. Oh et al [20] reported that the incidence of AD was negatively correlated with the intake of antioxidant nutrients (including retinol and β-carotene), and Mihály et al [21] found decreased retinoid concentration and retinoid signalling pathways in human AD patients. Our previous studies demonstrated that VA and VD co-deficiency may exacerbate the symptoms of children with autism spectrum disorders [22].…”
Section: Introductionmentioning
confidence: 99%
“…The present results are important because the inflammatory status of the subjects was associated with inadequate plasma β-carotene levels, a situation that could increase the risk of developing diabetes or metabolic syndrome [1,2,3,4]. Furthermore, our findings also have important implications because, as reported by other authors, it seems unwise to interpret biomarker data as prima facie evidence of dietary intake without a more complete understanding of the physiological processes that affect nutrient plasma levels [14], such as the inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…β-Carotene has antioxidant activity and has been related to the prevention of allergies, diabetes and metabolic syndrome; therefore, maintaining an adequate β-carotene status from childhood onward is vital [1,2,3,4]. Nevertheless, a remarkable prevalence of β-carotene deficiency has been reported in children (41.5%) [5] and adolescents (25%) [6].…”
Section: Introductionmentioning
confidence: 99%
“…This highlights the link between the microbiome, intestinal inflammation and allergic disease and the potential utility of monitoring gut health for predictive biomarkers in multiple disease settings. Similarly, nutritional status could be monitored through biomarkers 60 as could environmental exposures that effect disease manifestation 61 . Candidate approaches have also been undertaken using umbilical cord blood.…”
Section: Allergymentioning
confidence: 99%